Induced symmetric 2D Mesoporous Graphitic Carbon Spinel Cobalt Ferrite (CoFe2O4/2D-C) with high porosity fabricated via a facile and swift sucrose templated microwave combustion route for an improved supercapacitive performance. (January 2021) - Otabil Bonsu, Jacob; Appiagyei, Alfred Bekoe; Han, Jeong In
Graphical abstract: Highlights: A facile and swift sucrose templated microwave combustion synthesis approach is employed for the fabrication of CoFe2 O4 /2D-C. Porous morphology is obtained for CoFe2 O4 /2D-C which enhanced the electrode materials performance. A high specific capacitance of 1318.1 Fg −1 and energy density of 77.3 W h kg −1 was obtained. Power law suggests the storage mechanism for CoFe2 O4 /2D-C is influenced congruently by both the capacitive and diffusive controlled process. Carbon coating spinel ferrites with sucrose yielded a symmetric resonating single layer 2D graphitic carbon. Abstract: Symmetric 2D Mesoporous Graphitic Carbon spinel cobalt ferrite (CoFe2 O4 /2D-C) with high porosity has been fabricated via a facile and swift sucrose template microwave combustion process followed by an additional annealing treatment. The CoFe2 O4 /2D-C composite comprises carbon coated spinel cobalt ferrite with densely connected porous layered structure facilitating fast electron and ion transport. Benefiting from such an inimitable structure, CoFe2 O4 /2D-C is employed as supercapacitors electrode material and exhibited a high specific capacitance (1318.1 Fg −1 at 2.5 A g −1 current density) and energy density (77.3 W h kg −1 ) with an excellent electrochemical capacity retention of 97.2 % after 4000 cycles. Power law which expresses the dependence of peak CV current on scan rate at fixed potential confirmed that, the charge storage mechanism for the electrode material (CoFe2 O4 /2D-C) is influenced congruently by both the capacitive and diffusive controlled process which promoted an efficient energy storage for CoFe2 O4 /2D-C. Accordingly, this outstanding performance put forward its application as an effective material for electrochemical capacitors.